Periodic paralysis across the life course: age-related phenotype transition and sarcopenia overlap - Suetterlin, Karen; Law, Sinead; Arnold, William David (Frontiers in Neurology, 2024)
In Periodic Paralysis (PP), a rare inherited condition caused by mutation in skeletal muscle ion channels, the phenotype changes with age, transitioning from the episodic attacks of weakness that give the condition its name, to a more degenerative phenotype of permanent progressive weakness and myopathy. This leads to disability and reduced quality of life. Neither the cause of this phenotype transition, nor why it occurs around the age of 40 is known. However, 40 is also the age of onset of ‘normal’ age-related physiological decline when we consider (a) muscle mass and strength (b) physical function at the world class level and (c) age-related mitochondrial dysfunction. Elevated Na+, mitochondrial dysfunction and sarcoplasmic Ca2+ leak via the skeletal muscle ryanodine receptor (RyR1) have been implicated in both periodic paralysis myopathy and skeletal muscle ageing. We suggest this combination may trigger a negative spiral ultimately leading to progressive muscle failure. Understanding the interaction between ageing physiology and disease phenotype will provide a window into the healthy ageing process but also help understand how, and why PP phenotype changes with age. Understanding the mechanism underlying PP phenotype-transition and its link with ageing physiology, not only has the potential to identify the first disease modifying therapies for PP, but also to identify novel and potentially tractable mechanisms that contribute to sarcopenia, the pathological loss of muscle mass and function with age.